2022
DOI: 10.1002/wcs.1603
|View full text |Cite
|
Sign up to set email alerts
|

Imagination and social cognition in childhood

Abstract: Imagination is a cognitive process used to generate new ideas from old, not just in the service of creativity and fantasy, but also in our ordinary thoughts about alternatives to current reality. In this paper I argue for the central function of imagination in the development of social cognition in infancy and childhood. In section 1 I review a work showing that even in the first year of life, social cognition can be viewed through a nascent ability to imagine the physical possibilities and physical limits on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 102 publications
0
7
0
Order By: Relevance
“…Indeed, when asked to directly compare two options, children of this age—but not younger children—consistently identified the character with the counterfactual option as being nicer/meaner (in study 1) or definitely nice/mean (in study 2) than the one without a choice. It is also plausible that children's conceptual knowledge of the specific story elements in each study may have influenced their consideration of the relevant counterfactuals (e.g., Kominsky et al, 2021; Kushnir, 2022), and this could be an interesting direction for future research to explore. Overall, however, 6‐ to 7‐year‐olds clearly showed that they are able to consider what characters could have chosen to do.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, when asked to directly compare two options, children of this age—but not younger children—consistently identified the character with the counterfactual option as being nicer/meaner (in study 1) or definitely nice/mean (in study 2) than the one without a choice. It is also plausible that children's conceptual knowledge of the specific story elements in each study may have influenced their consideration of the relevant counterfactuals (e.g., Kominsky et al, 2021; Kushnir, 2022), and this could be an interesting direction for future research to explore. Overall, however, 6‐ to 7‐year‐olds clearly showed that they are able to consider what characters could have chosen to do.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper we consider both subcategories as valuable manifestations of imagination, and consequently, adopt the more general definition, suggested by Kushnir (2022), of imagination as the 'act of generating, from bits of old knowledge, new ideas and new possibilities'. This definition to a great extent aligns with the definition of imagination in the Merriam-Webster Dictionary (2023) ('an act or power of forming a mental image of something not present to the senses or never before wholly perceived in reality'), as well as the definition in the Oxford Dictionary of Philosophy (2023) ('the ability to create and rehearse possible situations, to combine knowledge in unusual ways, or to invent thought experiments').…”
Section: The Development Of Imaginationmentioning
confidence: 99%
“…Although the relations with age suggest the need to examine age-related cognitive and socio-emotional factors in children's attributions of emotional valence to God, the reciprocal pathway is also critical to be understood. Prior research has begun to delineate the developmental affordances of children's engagement with other abstract beings in their fantasy play (Gilpin et al 2015;Seja and Russ 1999) and imagination (Kushnir 2022;Thibodeau-Nielsen et al 2021). It may be that the experience of engaging with an abstract being, such as God, can provide children the cognitive space to not only practice exploring their own emotional capacity, but also the emotional capacities of others.…”
Section: Limitations and Future Researchmentioning
confidence: 99%